The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsami.1c14505
|View full text |Cite
|
Sign up to set email alerts
|

A Passive Fuel Cell Fed with an Electrically Rechargeable Liquid Fuel

Abstract: Passive fuel cells, using diffusion and natural convection for fuel delivery, are regarded as promising candidates for powering portable devices including mobile phones and laptops. However, the performance of passive fuel cells which employ typical liquid alcohol fuels are still limited, which thereby greatly hampered their commercialization progress. Recently, a novel concept named the electrically rechargeable liquid fuel (e-fuel), with its rechargeability, cost-effectiveness, and superior reactivity, has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It also indicated that palladium catalyst had high activity for formic acid oxidation at very low anode potential. The cell voltage was recorded to be well above 0.8 V. R.I Masel et al, also reported that the current density of the cell increased to 0.63 A, on using Palladium Black Anode as the catalyst, which was 200 times higher, when using a Platinum Catalyst at 0.4 V. The CV [313] (Reproduced with permission from reference 315, American Chemical Society, 2021) measurements carried out for palladium Black indicated a big anodic oxidation peak at 0.3 V. It was also reported that, on operating the DFAFC at 50°C, a maximum power density of 375 mW/cm 2 was achieved. [311] Kenis et al reported the performance output of a Si-Based DFAFC, where the fuel and oxidants are fed to the electrodes in a passive way, that is the liquid formic acid is in contact with the anodic part (Pd or Pt Catalyst) of MEA and on the other side, quiescent air is fed to the cathode (Pt Catalyst) which is more of an air breather setup.…”
Section: Unsupported Pt and Pd Based Catalystsmentioning
confidence: 82%
See 1 more Smart Citation
“…It also indicated that palladium catalyst had high activity for formic acid oxidation at very low anode potential. The cell voltage was recorded to be well above 0.8 V. R.I Masel et al, also reported that the current density of the cell increased to 0.63 A, on using Palladium Black Anode as the catalyst, which was 200 times higher, when using a Platinum Catalyst at 0.4 V. The CV [313] (Reproduced with permission from reference 315, American Chemical Society, 2021) measurements carried out for palladium Black indicated a big anodic oxidation peak at 0.3 V. It was also reported that, on operating the DFAFC at 50°C, a maximum power density of 375 mW/cm 2 was achieved. [311] Kenis et al reported the performance output of a Si-Based DFAFC, where the fuel and oxidants are fed to the electrodes in a passive way, that is the liquid formic acid is in contact with the anodic part (Pd or Pt Catalyst) of MEA and on the other side, quiescent air is fed to the cathode (Pt Catalyst) which is more of an air breather setup.…”
Section: Unsupported Pt and Pd Based Catalystsmentioning
confidence: 82%
“…Figure 13. (a) Working principle (b) Hardware components (c) Fabrication of a of a passive fuel cell[313] (Reproduced with permission from reference 315, American Chemical Society, 2021)…”
mentioning
confidence: 99%
“…During the test, the e-fuel was delivered to the anode by a peristaltic pump at a flow rate of 60 mL min –1 from a tank of 120 mL e-fuel, while pure oxygen was fed to the cathode at a flow rate of 10 sccm. The polarization curve tests were conducted using other homemade active and passive fuel cells, as reported before, both of which have an active area of 2.0*2.0 cm 2 . For the active fuel cell, the e-fuel and the oxygen were fed into the cell at 60 mL min –1 and 10 sccm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For the active fuel cell, the e-fuel and the oxygen were fed into the cell at 60 mL min –1 and 10 sccm, respectively. While for the passive fuel cell, a current collector with an open ratio of 70% was adopted . Both cells used 20 mL of e-fuel during the tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation